Influence of the production environment on the cultivation of lettuce and arugula with spent mushroom substrate - Zied, Diego C. [UNESP]; de Abreu, Carlos G.; da S. Alves, Lucas [UNESP]; Prado, Evandro P. [UNESP]; Pardo-Gimenez, Arturo; de Melo, Paulo C.; Dias, Eustáquio S. (Elsevier, 2021)
After mushroom production, the substrate plus the cultivated mycelium represents a byproduct, the so-called “spent mushroom substrate” (SMS). We evaluated different SMS types in fresh form, recently taken from the cultivation rooms, for the production of lettuce and arugula in the open field, greenhouse and greenhouse in pot. Three kinds of SMS were used (i - SMS of ABL (Agaricus subrufescens), ii - SMS of POS (Pleurotus ostreatus) and iii - 50% SMS of ABL + 50% SMS of POS) at three doses (1, 2 and 4 kg m−2). For comparison purposes, two commercial soil conditioners, Forth Condicionador® and Visa Fértil Orgânico®, were used. Finally, chicken manure with reference as international organic material was used. A control treatment consisted of a soil plot without any organic material. The application of fresh SMS in the production of LE (lettuce) and AR (arugula) is feasible considering several agronomic parameters evaluated, therefore that in F (field) the superior results were obtained by the ABL dose of 4 kg m−2, in the GR (green house) at a lower dose ABL with 1 kg m−2, POS with 2 kg m−2 and mix with ABL + POS at doses of 2–4 kg m−2, and finally in GR/P (greenhouse pot) it was proved that in a protected environment by rain the combination ABL + POS at dose of 4 kg m−2 is recommended.
Keywords: Chicken manure; Commercial soil conditioners; Eruca sativa; Fresh compost; Lactuca saliva